A realidade do sistema de bibliotecas de uma Universidade Pública do Estado do Amazonas no uso de recursos de tecnologia assistiva para o atendimento aos usuários com deficiência visual e auditiva - Vasconcelos, Kátia Maria Melo de (2022)
The scope of this work is the assistive technology resources used in a university library system. The guiding question of the research sought to know about the functionality of this library system in offering accessibility to users with visual and hearing impairments and which ones should be added to make it more inclusive, considering the needs of these users. The general objective was defined: to evaluate the use of assistive technology by the library system of a public university in the State of Amazonas. The research has an exploratory and descriptive character, of a qualitative nature, and the methodology applied was bibliographic and field. The data obtained for the analysis of the research were collected through a case study, carried out through a questionnaire created in Google Forms, with closed questions following the methodology of the Likert Scale, and which reached the interviewees via email from the Gmail. The main results found that there is a lack of assistive technology resources in university libraries and that the products and services offered by them are not sufficient and are not adequate to meet the informational needs of people with visual and hearing impairments. It was also contacted the lack of funds directed to libraries for the acquisition of these resources. In view of this reality, it was suggested to search for incentives for the acquisition of assistive technology in order to equip libraries so that their products and services are accessible to all users, regardless of the existence or not of a disability. It was also suggested some AT to help people with visual and hearing impairments.